Effect of control release fertilizer (CRF) on growth media for oil palm seedlings (Elaeis guineensis) growth - Harman, Mohammad Fikri (2015)
Fertilizer is an important input that supplies nutrients to plants for their optimum growth and production. In oil palm plantation, large amount of fertilizers is required and commonly fertilizers are easily leached off and promote wastage especially if they are applied at higher rates. Control Release Fertilizer (CRF) are claimed to be able to replace or become alternative to the conventional fertilizers and to increase efficiency of nutrient uptake, an appropriate fertilization should be done at the main nursery stage. The objective of this study is to determine the optimum rate of control release fertilizer for oil palm seedlings growth comparing them with the standard conventional fertilizers at the main stage of nursery. This experimental design that was used is Complete Randomized Design (CRD) with four treatments: T1 is a control treatment using NPK Blue (12:12:17:2) whereas T2, T3 and T4 each, using SK COTE® Precise (19-10-13+2.5MgO+TE) at 25g/bag, 50g/bag and 75g/bag respectively. There were two different sources of oil palm seedlings used which were from Sime Darby and FELDA with four replications. The parameters that were collected in this experiment are oil palm height, frond length, root dry weight, top dry weight and top fresh weight for quantitative measurement. While for qualitative measurement, N, P, K contents will be analyzed using Auto Analyzer (AA) and Atomic Absorption Spectrophotometer (AAS). Analysis of data will be used is the Statistical Analysis System (SAS) and Least Significant Difference (LSD) for mean comparison.